Fungsi Harta Menurut Al-Qur'an - Abdul Karim (Al-Hikmah Journal for Religious Studies, 2011)
Treasure in the Qur'an referes to as al-mal or al-amwal (in the plural). These words (al-mal or al-amwal) get big attention in the Qoran so that it has been repeated as many as 86 times. According to Islam, the properties or treasure of people should be used for human life, such as paying employee wages, returning the loan, paying zakat, he dowry, and so on. Moreover, the treasure should be spent to strengthen kinship (ukhuwah), and to overcome the gap between the aghniya (the rich) and dhu'afa (the poors). In general, it can be concluded that Islam pushes the use of treasure to do good thing that leads to realize a prosperous society, and equity